Microbe-enriched compost application on germination substrates of Beilschmiedia roxburghiana, Bouea oppositifolia and Syzygium polycephalum - HENDRA HELMANTO; FRISCA DAMAYANTI; DIAN LATIFAH (Nusantara Bioscience, 2017)
Helmanto H, Damayanti F, Latifah D. 2017. Microbe-enriched compost application on germination substrates of Beilschmiedia roxburghiana, Bouea oppositifolia and Syzygium polycephalum. Nusantara Bioscience 9: 300-305. The success of germination has been an important issue in many forest restoration programs; that is mainly affected by the quality of sowing media. Application of Bioposka compost (microbe-enriched compost) in the sowing media was hypothesized to increase the success of the germinating and transplanting also. The research aimed at investigating the effect of Bioposka compost to the germination and the seedling growth of the study species. The complete-randomized research design was used for three sowing media, i.e., sand, Bioposka compost and the mixture of sand: compost (1: 1 ratio) of tree species i.e., Syzygium polycephalum, Bouea oppositifolia and Beilsmedia roxburghiana. The variables observed were total and normal germination capacity, first germination, final germination, germination rate, germination simultaneity and seedling growth. The results were analyzed using STAR (Statistical Tool for Agricultural Research). In addition, the microbial abundance of bacteria, fungi, and yeast in each media were calculated using the spread-plate methods. The germination and seedling growth responses were varied between the different media. The germination capacity and seedling growth of Syzygium polycephalum and Bouea oppositifolia were lower by microbe-enriched compost. By contrast, the germination capacity and the seedling growth of Beilsmedia roxburghiana were not significantly different. Moreover, the microbe-enriched compost application increased the abundance of bacteria, fungi, and yeast in the media.